2015
DOI: 10.1186/s40360-015-0010-4
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal effect of the benzyl ester of N-propyl oxamate: a bi-potential prodrug for the treatment of experimental Chagas disease

Abstract: BackgroundChagas disease, which is caused by Trypanosoma cruzi, is a major health problem in Latin America, and there are currently no drugs for the effective treatment of this disease. The energy metabolism of T. cruzi is an attractive target for drug design, and we previously reported that inhibitors of α-hydroxy acid dehydrogenase (HADH)-isozyme II exhibit trypanocidal activity. N-Propyl oxamate (NPOx) is an inhibitor of HADH-isozyme II, and its non-polar ethyl ester (Et-NPOx) is cytotoxic to T. cruzi. A ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 47 publications
(72 reference statements)
1
17
0
1
Order By: Relevance
“…Nevertheless it may furnish significant insights for the infection chemotherapy, as β-lapachone was reported to produce similar alterations in T. cruzi epimastigotes, amastigotes and trypomastigotes (Docampo et al., 1978), the developmental forms that multiply within mammalian host cells and spread via blood, respectively. In addition, different antiparasitic compounds may display similar effects upon epimastigotes and trypomastigotes and/or amastigotes, the developmental forms (Urbina et al., 1988, Urbina et al., 1993; Moreira et al., 2013a; Costa et al., 2011, Azeredo et al., 2014, Díaz et al., 2014; Jimenez et al., 2014; Veiga-Santos et al., 2014, Britta et al., 2015, Meira et al., 2015, Volpato et al., 2015, Beer et al., 2016) and the epimastigotes may therefore comprise and/or take part in experimental models (Kessler et al., 2013, Benítez et al., 2014, Sangenito et al., 2014, Wong-Baeza et al., 2015, Khare et al., 2015, Pessoa et al., 2016, Valera Vera et al., 2016). Thus, numerous studies perform screening experiments with epimastigotes and/or trypomastigotes further approach the selected active compounds in intracellular amastigotes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless it may furnish significant insights for the infection chemotherapy, as β-lapachone was reported to produce similar alterations in T. cruzi epimastigotes, amastigotes and trypomastigotes (Docampo et al., 1978), the developmental forms that multiply within mammalian host cells and spread via blood, respectively. In addition, different antiparasitic compounds may display similar effects upon epimastigotes and trypomastigotes and/or amastigotes, the developmental forms (Urbina et al., 1988, Urbina et al., 1993; Moreira et al., 2013a; Costa et al., 2011, Azeredo et al., 2014, Díaz et al., 2014; Jimenez et al., 2014; Veiga-Santos et al., 2014, Britta et al., 2015, Meira et al., 2015, Volpato et al., 2015, Beer et al., 2016) and the epimastigotes may therefore comprise and/or take part in experimental models (Kessler et al., 2013, Benítez et al., 2014, Sangenito et al., 2014, Wong-Baeza et al., 2015, Khare et al., 2015, Pessoa et al., 2016, Valera Vera et al., 2016). Thus, numerous studies perform screening experiments with epimastigotes and/or trypomastigotes further approach the selected active compounds in intracellular amastigotes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here represent one of the most comprehensive studies to date. Other studies have used high doses of the drug, obtaining conflicting results, while Bustamante et al (2014) obtained a 95 to 100% cure rate at 100 mg/kg in a continuous or intermittent protocol applied in C57BL/6 (Ly5.2) mice and Wong-Baeza et al (2015) obtained a slight decrease in parasitaemia with the same dose for 50 days in NIH albino mice. This discrepancy may be explained by the strains of mice used; however, the response could also depend on the assayed strain of T. cruzi , which is apparent from the work of Andrade et al (1985) , who found that type I strains (high and early parasitaemia with macrophage tropism) had high susceptibility (56 ± 16% cure), type II strains (high and late parasitaemia with heart tropism) had medium to high susceptibility (52 ± 11% cure), and type III strains (low parasitaemia with skeletal muscle tropism) had low susceptibility (0.45 ± 0.45% cure) to therapeutic schemes based on Nfx 200 mg/kg for four days followed by 50 mg/kg for five days/week for 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…The high lipophilicity from B-NPOx compared to Et-NPOx, facilitates a better penetration into T. cruzi, resulting in the enzymatic cleavage of B-NPOx and the releasing of NPOx and benzyl alcohol as potential trypanocidal agents. These results in conjunction with its low toxicity, suggest that B-NPOx could be used as a potent prodrug for the treatment of Chagas disease [677].…”
Section: O Benzyl Ester Of N-propyl Oxamate When Inhibitors Ofmentioning
confidence: 91%